1981
DOI: 10.1161/01.res.49.1.89
|View full text |Cite
|
Sign up to set email alerts
|

Effects of myocardial ischemia on quantitative ultrasonic backscatter and identification of responsible determinants.

Abstract: Quantitative characterization of myocardial properties represent a rapidly emerging area of echocardiographic investigation. Because measurement of the ultrasonic integrated backscatter is theoretically applicable to analysis in vivo with reflected ultrasound, this study was performed to develop and evaluate a suitable method for measurement of quantitative backscatter in vivo. In view of the desirability of characterizing ischemic myocardium noninvasively, the study was performed with animal preparations simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(28 citation statements)
references
References 15 publications
1
27
0
Order By: Relevance
“…Thus, a variable must be free of any angle dependence with respect to the region of interest and free from attenuation effects. An absolute measurement such as mean backscatter power, which has been used by several investigators, 22,23,28,29 has certain reference difficulties that potentially limit its clinical usefulness. On the other hand, relative measurements such as the cyclic backscatter power and the phase relationship may be useful in the clinical environment.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a variable must be free of any angle dependence with respect to the region of interest and free from attenuation effects. An absolute measurement such as mean backscatter power, which has been used by several investigators, 22,23,28,29 has certain reference difficulties that potentially limit its clinical usefulness. On the other hand, relative measurements such as the cyclic backscatter power and the phase relationship may be useful in the clinical environment.…”
Section: Discussionmentioning
confidence: 99%
“…Interstitial and intracellular edema, alterations in the calcium and collagen contents of ischemic tissue, intramyocardial blood volume and intrinsic myocardial contractile function have been cited as possible determinants. 24,28) The magnitude of such variation has been shown to be related to the severity of ischemia. CVIBS is blunted promptly by ischemia and is augmented after reperfusion in animals and humans.…”
Section: A B Discussionmentioning
confidence: 99%
“…This implies that IB is a measure of the mean reflected ultrasonic energy from a particular region of tissue [4] . The aspect of myocardial tissue characterization which has aroused most interest has been the potential predictive value of the cyclic variation (CV) of IB for determining myocardial viability, initially described in vivo in animal models [5][6][7][8][9] . This work has also been reproduced in the clinical setting [10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…Extensive clinical evaluation of the properties of myocardial IB has demonstrated that the magnitude, cycledependent variation and the timing of peak and trough IB levels are all influenced by a wide range of disease processes [5,26] . In these studies, IB values were determined by either off-line processing of the acquired (RF) signal or by on-line processing using dedicated hardware incorporated in standard clinical equipment.…”
Section: Introductionmentioning
confidence: 99%